2002
DOI: 10.1088/0022-3727/35/20/323
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution characterization of piezoelectric ceramics by ultrasonic scanning force microscopy techniques

Abstract: The local elastic properties and the ferroelectric domain configuration of piezoelectric ceramics have been examined by atomic force acoustic microscopy and by ultrasonic piezoelectric force microscopy. The contrast mechanisms of the two techniques are discussed. From the local contact stiffness which is obtained by evaluation of the contact resonance spectra, the elastic constants of the sample surface can be calculated. In the case of anisotropic materials these elastic constants correspond to the indentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
113
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(117 citation statements)
references
References 41 publications
(65 reference statements)
3
113
0
1
Order By: Relevance
“…22 In our previous publications, we presented in-depth analysis of the static (low frequency) PFM imaging mechanism and demonstrated approaches for data interpretation and visualization. 12,23,24 In particular, we have shown that under the condition of good tip-surface contact (no potential drop in the tip-surface gap), materials properties measured by PFM are independent of the geometric characteristics of the tip, thus distinguishing this technique from mechanical SPM probes such as Atomic Force Acoustic M icroscopy 25 or Ultrasonic Force M icroscopy 26,27 that require that the tip shape be calibrated for quantitative measurements. This suggests that PFM is relatively insensitive to surface topography and provides quantitative information on material properties without the stringent requirement for tip shape calibration.…”
Section: Introductionmentioning
confidence: 99%
“…22 In our previous publications, we presented in-depth analysis of the static (low frequency) PFM imaging mechanism and demonstrated approaches for data interpretation and visualization. 12,23,24 In particular, we have shown that under the condition of good tip-surface contact (no potential drop in the tip-surface gap), materials properties measured by PFM are independent of the geometric characteristics of the tip, thus distinguishing this technique from mechanical SPM probes such as Atomic Force Acoustic M icroscopy 25 or Ultrasonic Force M icroscopy 26,27 that require that the tip shape be calibrated for quantitative measurements. This suggests that PFM is relatively insensitive to surface topography and provides quantitative information on material properties without the stringent requirement for tip shape calibration.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] By modulating the tip-sample contact with an ultrasonic frequency oscillation, these methods show potential applications in reliable and accurate characterizations of elastic properties with nanoscale resolution. [6][7][8][9][10][11][12] In CR-AFM, either or both the tip and the sample are vibrated with an ultrahigh frequency while the tip contacting the sample surface. By measuring the contact resonances of the cantilever, and by employing appropriate theoretical models, the local contact stiffness and, subsequently, the local elastic modulus can be obtained quantitatively.…”
mentioning
confidence: 99%
“…11,12,14 However, possible effects of geometry-induced contrast variations have not been adequately considered. Here, we investigated the effects of sample topography on UAFM imaging and multiple contrast inversions along with the gradual increase of modulation frequency were observed.…”
mentioning
confidence: 99%
“…[36][37][38][39][40] Several studies combine PFM and other localized characterizations, such as atomic force acoustic microscopy (AFAM) 41,42 by Zhou and Li et al, 71 and confocal Raman microscopy 72 and Raman spectroscopy. 73 In particular, combination of PFM and AFAM allows direct insight into the coupling between mechanical and ferroelectric properties, and hence fundamental mechanics of ferroelectric materials [43][44][45][46][47][48][49] Finally, the review by Barrett et al 74 reports systematic studies of polarization controlled surface electronic properties and domain structures on ferroelectric surfaces using a variety of electron imaging and structural probes. These studies provide much needed insight into the electronic properties of ferroelectric surfaces, complementing recent advances in X-ray scattering in reactive environment achieved by Argonne group.…”
mentioning
confidence: 99%